Public Service Quality in Population Administration Services - Adelina, Sabrina Elliya; Martono, S. (Economic Education Analysis Journal, 2021)
This study aimed to test the service quality of the independent variable, namely public services on the dependent variable, namely population administration services. The population in this study were all people who provided services in the sub-districts of Salatiga. The sampling technique in this study used incidental sampling. The number of samples in this study was obtained through calculations with the iteration formula and the number of samples who became respondents was 115 people. Data collection methods used questionnaires, observation, interviews and documentation. The data analysis technique used quantitative descriptive analysis with the index number formula. The results showed that the Total Index Average was 81.37%. The size of the average index number for each dimension, namely the tangible dimension (physical evidence) of 68.97%, reliability of 69.04%, responsiveness of 77.8%, assurance (guarantee) of 74, 25%, and empathy of 72.93%. The results of this study indicated that people who were visitors to the districts in the city of Salatiga had a moderate view of service quality. This was because the quality of sub-district services in Salatiga had not been maximized. Services in the sub-districts of Salatiga were in the medium category.